Study Of Menstrual Pattern and Menstrual Hygiene Practices Among Adolescent Girls - Hemlata G Rokade; Anjali P Kumavat (Medsci Publications, 2016)
Background: Menstrual hygiene and management will directly contribute to MDG-2 and MDG-3. This study was conducted to know the awareness about menstruation before menarche and the source of information; to compare menstrual pattern and menstrual hygiene among adolescent girls from slum and non-slum area and also to find some socio-demographic determinants of menstrual hygiene. Methods: A cross sectional study was conducted among 324 late adolescent girls, 200 from slum and 124 from non-slum. House to house survey was done. Results: Awareness of menstruation before menarche was seen in 56.48% girls. Friends [38.8%] and mothers [38.25%] were the main informant. The difference in mean age of menarche [12.85±1.13 in slum and 13.12±1.15 in non-slum] and regularity of cycles [126(63%) in slum and 102(82.26%) in non-slum] was statistically significant, p<0.05. 34% girls from slum and 45.97% from non-slum areas were practicing menstrual hygiene and this difference was statistically significant, p<0.05. Literacy status of adolescent girls was found to be the determinant of menstrual hygiene. Conclusion: Menstrual hygiene is an issue which needs to be addressed to all adolescent, with special emphasis in slum area. More emphasis should be given on improving adolescent literacy for achieving hygienic menstrual practices.